1998
DOI: 10.1007/s004210050358
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen uptake does not increase linearly at high power outputs during incremental exercise test in humans

Abstract: A group of 12 healthy non-smoking men [mean age 22.3 (SD 1.1) years], performed an incremental exercise test. The test started at 30 W, followed by increases in power output (P) of 30 W every 3 min, until exhaustion. Blood samples were taken from an antecubital vein for determination of plasma concentration lactate [La-]pl and acid-base balance variables. Below the lactate threshold (LT) defined in this study as the highest P above which a sustained increase in [La-]pl was observed (at least 0.5 mmol x l[-1] w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
58
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 28 publications
5
58
2
Order By: Relevance
“…In the present study, we confirm previous observations that S 2 is steeper than S 1 in normal subjects, probably reflecting the contribution of the O 2 slow component (2,3,5,29). This pattern, however, contrasted with that found in patients with MM who showed a consistently lower S 2 /S 1 ratio at the same pedaling rate compared to normal subjects.…”
Section: Determinants Of the δ O 2 /δWr Relationship In MM Patientssupporting
confidence: 89%
See 2 more Smart Citations
“…In the present study, we confirm previous observations that S 2 is steeper than S 1 in normal subjects, probably reflecting the contribution of the O 2 slow component (2,3,5,29). This pattern, however, contrasted with that found in patients with MM who showed a consistently lower S 2 /S 1 ratio at the same pedaling rate compared to normal subjects.…”
Section: Determinants Of the δ O 2 /δWr Relationship In MM Patientssupporting
confidence: 89%
“…As mentioned, the Δ O 2 /ΔWR relationship (mL·min -1 ·W -1 ) was calculated to obtain an index of the overall gain of the O 2 response, i.e., in disease states, reduced values would indicate a greater reliance on anaerobic sources of ATP regeneration (1,2). Considering that the GET could distort the linearity of the response (due to an even greater reliance on anaerobic metabolism) (3,5), the Δ O 2 /ΔWR slope was determined using linear regression analysis over three segments: S 1 , from the start of O 2 increase during exercise to the GET; S 2 , from the GET to either peak O 2 or where O 2 began to level off, and S T , over the range of S 1 + S 2 .…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, VO 2 max values obtained from gradual protocols can be significantly higher (9-17%) than the expected VO 2 at the final workload predicted from the previous linear relationship between VO 2 and workload below the LT [4,6,7].Although some reports have studied the etiology of this nonlinear increase in the VO 2 :power output relationship during incremental exercise (also termed "excess" VO 2 ) [1][2][3][4][5][6][7], some controversy exists and more research is needed. Jones et al…”
mentioning
confidence: 99%
“…
Previous research with healthy, not highly trained humans has shown that the VO 2 :workload relationship shows a nonlinear increase after the lactate threshold (LT) is exceeded during incremental exercise tests [1][2][3][4][5][6][7]. For instance, VO 2 max values obtained from gradual protocols can be significantly higher (9-17%) than the expected VO 2 at the final workload predicted from the previous linear relationship between VO 2 and workload below the LT [4,6,7].

Although some reports have studied the etiology of this nonlinear increase in the VO 2 :power output relationship during incremental exercise (also termed "excess" VO 2 ) [1][2][3][4][5][6][7], some controversy exists and more research is needed.

…”
mentioning
confidence: 99%